1996
DOI: 10.1002/j.1460-2075.1996.tb00630.x
|View full text |Cite
|
Sign up to set email alerts
|

Human hsp27, Drosophila hsp27 and human alphaB-crystallin expression-mediated increase in glutathione is essential for the protective activity of these proteins against TNFalpha-induced cell death.

Abstract: Expression of small stress proteins (shsp) enhances the survival of mammalian cells exposed to heat or oxidative injuries. Recently, we have shown that the expression of shsp from different species, such as human hsp27, Drosophila hsp27 or human alphaB‐crystallin protected murine L929 cells against cell death induced by tumor necrosis factor (TNFalpha), hydrogen peroxide or menadione. Here, we report that, in growing L929 cell lines, the presence of these shsp decreased the intracellular level of reactive oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
400
0
24

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 539 publications
(440 citation statements)
references
References 59 publications
16
400
0
24
Order By: Relevance
“…They suggested that radioresistance is due to an effect of HSP on the glutathione redox cycle, by facilitating the reduction of oxidised glutathione (GSSG) to GSH. 15 Also, Mehlen et al 16 reported that HSP27 raised the level of intracellular glutathione in response to TNF␣ and suggested a similar effect in response to other oxidative stress. Thus, it is not unlikely that upregulation will occur in response to radiation and result in radioresistance as the case is with HSP25.…”
Section: Discussionmentioning
confidence: 96%
“…They suggested that radioresistance is due to an effect of HSP on the glutathione redox cycle, by facilitating the reduction of oxidised glutathione (GSSG) to GSH. 15 Also, Mehlen et al 16 reported that HSP27 raised the level of intracellular glutathione in response to TNF␣ and suggested a similar effect in response to other oxidative stress. Thus, it is not unlikely that upregulation will occur in response to radiation and result in radioresistance as the case is with HSP25.…”
Section: Discussionmentioning
confidence: 96%
“…HSF1 and HSF2 are important for protecting cells from protein-damaging stress associated with misfolded proteins and aging as well as aging-related diseases (Rodgers et al, 2005;. Interestingly, Hsp27 has been shown to increase the cellular anti-oxidant defense (Mehlen et al, 1996). Elevated HSF1, HSF2 and Hsp27 levels reported here may indicate that muscle cells of aged animals respond to aging-related accumulation of oxidative stress and attempt to compensate the stress by increasing the amount of components required for the protective molecular machinery (Murlasits et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, in skeletal muscle, old animals seem to retain their capability to accumulate Hsp protein when subjected to heat shock . Both HSF1 and HSF2 are essential for protecting cells from protein-damaging stress associated with misfolded proteins and therefore aging (Ostling et al 2007;), whereas Hsp27 has been shown to increase the cellular anti-oxidant defense (Mehlen et al 1996). Elevated Hsp27, HSF1 and HSF2 levels reported here may indicate that muscle cells of aged HCR/LCR rats responded to aging-related accumulation of oxidative stress and attempted to compensate the stress by increasing the amount of protective molecular machinery in both of the studied rat lines (Murlasits et al 2006).…”
Section: Skeletal Muscle Propertiesmentioning
confidence: 99%
“…Diverse agents, such as TNFa, IL-1 and oxidative stress have been reported as potent modulators of mammalian Hsp27 phosphorylation (Arrigo and Landry, 1994). Overexpression of Hsp27 has been shown to protect cells against necrosis induced by anti-cancer drugs, TNFa or oxidative stress (Mehlen et al, 1995(Mehlen et al, , 1996a. Mammalian Hsp27 has also been shown to play a role in cell di erentiation (Shakoori et al, 1992).…”
Section: Introductionmentioning
confidence: 99%